Process Parameters Optimization of 14nm MOSFET Using 2-D Analytical Modelling - Noor Faizah Z.A.; Ahmad I.; Ker P.J.; Siti Munirah Y.; Mohd Firdaus R.; Md Fazle E.; Menon P.S. (EDP Sciences, 2023)
Hafnium oxides; High-k dielectric; Manufacture; Silicides; Taguchi methods; CMOS transistors; HIGH-K metal gates; Modeling and optimization; Process parameters; Process parameters optimizations; Titanium silicide; Tungsten silicide; Wafer fabrications; Reconfigurable hardware